Impact of Mandatory Preoperative Dental Screening on Infective Endocarditis in Patients Undergoing Surgical Valve Replacement - Lytfi Krasniqi, MD; Poul Erik Mortensen, MD; Emil Johannes Ravn, MD; Marlene Tofterup, MD; Henrik Nissen, MD, PhD; Christian Juhl Terkelsen, MD, PhD, DMSCi; Niels Holmark Andersen, MD, PhD, DMSCi; Ivy Modrau, MD, DMSCi; Kasper Stokbro, DDS, PhD; Jonas A. Povlsen, MD, PhD; Oke Gerke, MSc, PhD, DMSCi; Jesper Hallas, MD, DMSCi; et al. (JACC: Advances)
Background: Guidelines recommend preoperative dental screening (PDS) prior to surgical valve replacement (SVR) to reduce risk of prosthetic valve infective endocarditis (IE). Nonetheless, limited data support these recommendations. Objectives: The objective of this study was to investigate the impact of mandatory preoperative dental screening (MPDS) on risk of IE in patients undergoing SVR. Methods: Patients undergoing SVR in Western Denmark from 2020 to 2022 were included in this observational study. Patients were considered based on 2 applied PDS practices: MPDS, and no routine referral to preoperative dental screening (NPDS). Data were retrieved from Danish registries and adjudicated using medical records. The primary endpoint was incidence of IE. Secondary endpoints were all-cause mortality, and the composite endpoint of IE and all-cause mortality. Results: A total of 1,207 patients undergoing SVR were included. Of 805 patients in the MPDS, 93% (n = 751) underwent subsequent PDS, compared to 5% (n = 21) among 402 patients in the NPDS. Patients in the MPDS were older with higher rates of coexisting comorbidities. During a median follow-up of 2.6 years, 3.3% (n = 40) developed IE. The IE incidence rate for MPDS and NPDS was 16.0 (95% CI: 11.3-22.6) and 8.0 (95% CI: 4.0-16.0) per 1,000 person-years, respectively. Mortality rate was higher in MPDS (2-year mortality: 6.2% (95% CI: 4.7-8.1) vs 2.8% (95% CI: 1.6-5.0). Differences in IE rates, all-cause mortality but not composite endpoint were abolished in 370 propensity score-matched patients. Conclusions: Risk of IE was low regardless of PDS practice. MPDS prior to surgery did not alter the risk of IE or all-cause mortality in patients undergoing SVR in Denmark.